Answer:
(3 ± √23 * i) /4
Step-by-step explanation:
To solve this, we can apply the Quadratic Equation.
In an equation of form ax²+bx+c = 0, we can solve for x by applying the Quadratic Equation, or x = (-b ± √(b²-4ac))/(2a)
Matching up values, a is what's multiplied by x², b is what's multiplied by x, and c is the constant, so a = 2, b = -3, and c = 4
Plugging these values into our equation, we get
x = (-b ± √(b²-4ac))/(2a)
x = (-(-3) ± √(3²-4(2)(4)))/(2(2))
= (3 ± √(9-32))/4
= (3 ± √(-23))/4
= (3 ± √23 * i) /4
Answer:
A. 2 factors: 5 and (6+4x)
B. 5: 1 term
(6+4x): 2 terms
C: The coefficient is 4
Step-by-step explanation:
The factors are the parts of expression separate by multiplications, so there are 2 factors: 5 and (6+4x)
The terms of each factor are the terms separate by the sign + or -. So the term of the factor 5 is 1 and the terms of the factor (6+4x) are 6 and 4x
The coefficient of the variable term is the number that is beside the variable. The coefficient of x is 4.
Step-by-step solution:
7x + 3 + 6x + 11 = 0
7x + 6x + 11 + 3 = 0
13x + 11 + 3 = 0
13x + 14 = 0
13x = 0 - 14
13x = -14
x = -14 / 13
x = -1.077 approx.
Hope it helped,
BioTeacher101
Answer:
Okay to start with we know this side isn't congruent to our side with 55 degrees looking at this side we can see that x is not 95 degrees because it is an acute angle so A is crossed out. Next this side isn't congruent like I said so B is crossed out. C is possible but the angle wouldn't be as wide as it is if we had 59 degrees so C is incorrect. Leaving us with D 70 degrees hope this helps and sorry if I got it wrong!
Step-by-step explanation:
x^2 + y^2 - 6x - 4y - 12 = 0
x^2 - 6x + y^2 - 4y = 12
x^2 - 6x + 9 + y^2 - 4y + 4 = 12 + 9 + 4
(x - 3)^2 + (y - 2)^2 = 25